2017
DOI: 10.14238/pi56.5.2016.291-6
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin levels in non-obese, obese, and insulin resistant adolescents

Abstract: Background preterm infants are vulnerable to iron deficiency (ID) Background Adipose tissue is not merely a site for energy storage, but is also the largest endocrine organ, secreting various adipocytokines. plasma visfatin, an adipocytokine predominantly secreted from visceral adipose tissue, has insulin-mimetic effects, and has been closely linked to insulin resistance. Objective To compare plasma visfatin levels between obese and non-obese adolescents, as well as between obese adolecents with and without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Visfatin binds to the insulin receptor at a site differ from that of insulin and causes hypoglycemia by stimulating glucose utilization in adipocytes and myocytes and reducing glucose release from liver. [34] However, Fukuharaet al,(2005) and Li Hui-ling et al,(2015) found that Type 1 diabetic children and adolescents had a significantly lower Visfatin level compared to controls and no difference of serum Visfatin levels between the healthy and overweight children and the difference only was between the healthy and obese children [35,25],also Ihsan et al,(2017) published that overweight/obese individuals there was negative relation between Visfatin level and anthropometric and lipid profile parameters, which can be explained by functional healthy fat tissue in this early life time even in a group of patients with increased body fat. [36] In our study there was a significant difference between the obese children and healthy ones in the ultrasonographic findings of NAFLD and between the obese children and overweight ones with the frequency of 65.6% and 26.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Visfatin binds to the insulin receptor at a site differ from that of insulin and causes hypoglycemia by stimulating glucose utilization in adipocytes and myocytes and reducing glucose release from liver. [34] However, Fukuharaet al,(2005) and Li Hui-ling et al,(2015) found that Type 1 diabetic children and adolescents had a significantly lower Visfatin level compared to controls and no difference of serum Visfatin levels between the healthy and overweight children and the difference only was between the healthy and obese children [35,25],also Ihsan et al,(2017) published that overweight/obese individuals there was negative relation between Visfatin level and anthropometric and lipid profile parameters, which can be explained by functional healthy fat tissue in this early life time even in a group of patients with increased body fat. [36] In our study there was a significant difference between the obese children and healthy ones in the ultrasonographic findings of NAFLD and between the obese children and overweight ones with the frequency of 65.6% and 26.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid accumulation in the liver leads to hepatic inflammation and cytokine production. [36][37][38][39][40] Our results showed the ROC for serum Visfatin as a predictor of fatty liver in obesity, with sensitivity of 78.1% and specificity of 61.4% .…”
Section: Discussionmentioning
confidence: 96%
“…4 These Adipocytokines primarily regulates the body weight, food intake, insulin resistance, immunity and inflammatory activities. 5 Visfatin is a proinflammatory adipocytokine, also known as pre-ß cell colony-enhancing factor 1(pBEF-1). 6 This cytokine is a protein comprising nearly 500 amino acids, predominantly produced by the human visceral adipose tissues (VAT).…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in triglyceride metabolism and adipocyte proliferation. 5,7 Several studies have reported a significant association between serum visfatin level and obesity. 1,3,7 A study involving the Taiwanese population indicated that serum visfatin levels are closely linked with abdominal obesity and type 2 DM.…”
Section: Introductionmentioning
confidence: 99%